A UK-Wide Survey of Life-Threatening Thyroidectomy Complications. (13th January 2011) - Hassan-Smith, Z. K.; Gopinath, P.; Mihaimeed, F.
Abstract : Background and Aims . Complications following thyroidectomy can prolong hospital stay and cause significant morbidity particularly for patients treated for benign thyroid conditions. Our aim was to administer a UK-wide survey of thyroid surgery units on frequency and timing of the onset of life-threatening airway complications & correlate to factors that might be associated with them. Methods . A questionnaire including the number of and timing of the onset of life-threatening airway complications, number of thyroidectomy procedures performed per year, surgeon years of experience, the use of difficult airway management protocol, post-operative patient destination, and patient deaths, was sent to 80 UK surgical units. Results . 23/41 hospitals responded reported no postthyroidectomy airway complications. Life-threatening airways complications all occurred within the first 12 hours postoperatively, with 9 cases occurring in the recovery room and in less than 2 hours, 3 cases occurring 2–6 hours, and 3 cases occurring 6 to 12 hours after surgery. Conclusion . The results may support recent publications that advocate thyroidectomy as a less-than-24-hour surgery procedure in selected patients. Further a larger study and standardised protocol are required to establish patients' selection criteria to determine who are likely to develop serious postoperative complication and may require HDU bed.